Drivers and demographic consequences of seasonal mass changes in an alpine ungulate - Mathieu Douhard; Simon Guillemette; Marco Festa‐Bianchet; Fanie Pelletier (Ecology, 2018)
We know little about the determinants and demographic consequences of the marked seasonal mass changes exhibited by many northern and alpine mammals. We analysed 43 years of data on individual winter mass loss (the difference between mass in early June and mass in mid‐September the previous year) and summer mass gain (the difference between mass in mid‐September and in early June of the same year) in adult bighorn sheep ( Ovis canadensis ). We calculated relative seasonal mass change as a proportion of individual body mass at the start of each season. We first examined the effects of weather and population density on relative changes in body mass. We then assessed the consequences of relative seasonal mass changes on reproduction. Mean April–May temperature was the main driver of relative seasonal mass changes: warm springs reduced both relative winter mass loss and summer mass gain of both sexes, likely partially due to a trade‐off between growth rate of plants and duration of access to high‐quality forage. Because these effects cancelled each other, spring temperature did not influence mass in mid‐September. Mothers that lost relatively more mass during the winter had lambs that gained less mass during summer, likely because these females allocated fewer resources to lactation. Winter survival of lambs increased with their summer mass gain. In males, relative mass loss during winter, which includes the rut, did not influence the probability of siring at least one lamb, possibly indicating that greater mating effort did not necessarily translate into greater reproductive success. Our findings improve our understanding of how weather influences recruitment and underline the importance of cryptic mechanisms behind the effects of climate change on demographic traits.

The influence of birth date via body mass on individual fitness in a long‐lived mammal - Floriane Plard; Jean-Michel Gaillard; Tim Coulson; A. J. Mark Hewison; Mathieu Douhard; François Klein; Daniel Delorme; Claude Warnant; Christophe Bonenfant (Ecology, 2015)
The timing of birth has marked impacts on early life and early development of newborns in many species. In seasonal environments, early‐born offspring often survive and grow better than late‐born offspring, but despite the long‐lasting effects of early conditions on life history traits, the influence of birth date on fitness has rarely been investigated for long‐lived species. In this study, we analyzed both the short‐ and long‐term effects of birth date on individual life history traits and explored its subsequent impact on individual fitness in a population of roe deer. We considered both the direct effects, as well as the indirect effects of birth date mediated through the effects of body mass, on demographic parameters. We found that in addition to short‐term effects on early body growth and survival, birth date generates “silver spoon” effects on adult life history traits of female roe deer. Birth date had long‐lasting effects on female adult body mass such that early‐born females were, on average, 3 kg heavier as adults than late‐born females, although female adult survival was similar between these categories. Based on the observed relationships between birth date, body mass, and demographic parameters, we built an integral projection model describing the simultaneous distributions of birth date and body mass to quantify the fitness consequences of birth date. We found that the fitness of early‐born females was higher than that of late‐born females. These long‐lasting effects of birth date on fitness were mostly mediated through the influence of birth date on recruitment and adult body mass. By determining development of newborns during the early stages of life, birth date has a critical influence on each step of an individual's subsequent life history trajectory.

Variation in adult body mass of roe deer: early environmental conditions influence early and late body growth of females - Mathieu Douhard; Jean-Michel Gaillard; Daniel Delorme; Gilles Capron; Patrick Duncan; François Klein; Christophe Bonenfant (Ecology, 2013)
There is increasing evidence that environmental conditions experienced early in life can markedly affect an organism's life history, but the pathways by which early environment influences adult phenotype are poorly known. We used long‐term data from two roe deer ( Capreolus capreolus ) populations (Chizé and Trois‐Fontaines, France) to investigate the direct and indirect (operating through fawn body mass) effects of environmental conditions during early life on adult body mass. We found that environmental conditions (population size and spring temperatures) around birth influenced body mass of adult females through both direct and indirect effects in both populations. The occurrence of direct effects means that, for a given fawn body mass, adult female mass decreases with adverse conditions in early life. In contrast, we found no evidence for direct effects of early‐life conditions on adult body mass of males, suggesting the existence of sex‐specific long‐term responses of body mass to stressful early conditions. Our results provide evidence that early environmental conditions influence the adult phenotype through persistent effects over the body development in wild mammal populations.

How does climate change influence demographic processes of widespread species? Lessons from the comparative analysis of contrasted populations of roe deer - Jean‐Michel Gaillard; A. J. Mark Hewison; François Klein; Floriane Plard; Mathieu Douhard; Raziel Davison; Christophe Bonenfant (Ecology Letters, 2013)
How populations respond to climate change depends on the interplay between life history, resource availability, and the intensity of the change. Roe deer are income breeders, with high levels of allocation to reproduction, and are hence strongly constrained by the availability of high quality resources during spring. We investigated how recent climate change has influenced demographic processes in two populations of this widespread species. Spring began increasingly earlier over the study, allowing us to identify 2 periods with contrasting onset of spring. Both populations grew more slowly when spring was early. As expected for a long‐lived and iteroparous species, adult survival had the greatest potential impact on population growth. Using perturbation analyses, we measured the relative contribution of the demographic parameters to observed variation in population growth, both within and between periods and populations. Within periods, the identity of the critical parameter depended on the variance in growth rate, but variation in recruitment was the main driver of observed demographic change between periods of contrasting spring earliness. Our results indicate that roe deer in forest habitats cannot currently cope with increasingly early springs. We hypothesise that they should shift their distribution to richer, more heterogeneous landscapes to offset energetic requirements during the critical rearing stage.